IL-25 blockade inhibits metastasis in breast cancer - Zhujun Jiang (Protein & Cell, 2016)
Abstract Metastasis is the leading cause of death in breast cancer patients. However, the mechanisms underlying metastasis are not well understood and there is no effective treatment in the clinic. Here, we demonstrate that in MMTV-PyMT, a highly malignant spontaneous breast tumor model, IL-25 (also called IL-17E) was expressed by tumor-infiltrating CD4+ T cells and macrophages. An IL-25 neutralization antibody, while not affecting primary tumor growth, substantially reduced lung metastasis. Inhibition of IL-25 resulted in decreased type 2 T cells and macrophages in the primary tumor microenvironments, both reported to enhance breast tumor invasion and subsequent metastasis to the lung. Taken together, our data suggest IL-25 blockade as a novel treatment for metastatic breast tumor.